Independent and Combined Effects of Lactitol, Polydextrose, and Bacteroides thetaiotaomicron on Postprandial Metabolism and Body Weight in Rats Fed a High-Fat Diet - Olli, Kaisa; Saarinen, Markku T.; Forssten, Sofia D.; Madetoja, Mari; Herzig, Karl-Heinz; Tiihonen, Kirsti (Frontiers in Nutrition, 2016)
Obesity is related to the consumption of energy-dense foods in addition to changes in the microbiome where a higher abundance of gut Bacteroidetes can be found in lean subjects or after weight loss. Lactitol, a sweet-tasting sugar alcohol, is a common sugar-replacement in foods. Polydextrose, a highly branched glucose polymer, is known to reduce energy intake. Here, we test if the combined effects of lactitol or polydextrose in combination with Bacteroides species will have a beneficial metabolic response in rats fed a high-fat diet. 175 male Wistar rats were fed either a low-fat or high-fat diet. Bacteroides thetaiotaomicron (1010 bacteria/animal/day) was orally administered with or without lactitol (1.6−2 g/animal/day) or polydextrose (2 g/animal/day) for 8 days. Postprandial blood samples, cecal digesta and feces were collected on the last day. Measurements included: body weight, feed consumption, cecal short chain fatty acids, fecal dry matter and heat value, blood glucose, insulin, triglyceride, and satiety hormone concentrations. Lactitol and polydextrose decreased the mean body weight when administered with B. thetaiotaomicron or when lactitol was administered alone. Levels of postprandial plasma triglycerides declined with lactitol and polydextrose when administered with B. thetaiotaomicron. For intestinal hormone release, lactitol − alone or with B. thetaiotaomicron − increased the release of gastrointestinal peptide tyrosine tyrosine (PYY) as well as the area under the curve (AUC) measured for PYY (0−8 h). In addition, levels of insulin AUC (0−8 h) decreased in the lactitol and polydextrose supplemented groups. Lactitol and polydextrose may both provide additional means to regulate postprandial metabolism and weight management whereas the addition of B. thetaiotaomicron in the tested doses had only minor effects on the measured parameters.